2023
DOI: 10.3389/fnins.2023.1259473
|View full text |Cite
|
Sign up to set email alerts
|

The use of hyperbaric oxygen for veterans with PTSD: basic physiology and current available clinical data

Keren Doenyas-Barak,
Ilan Kutz,
Erez Lang
et al.

Abstract: Post-traumatic stress disorder (PTSD) affects up to 30% of veterans returning from the combat zone. Unfortunately, a substantial proportion of them do not remit with the current available treatments and thus continue to experience long-term social, behavioral, and occupational dysfunction. Accumulating data implies that the long-standing unremitting symptoms are related to changes in brain activity and structure, mainly disruption in the frontolimbic circuit. Hence, repair of brain structure and restoration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 108 publications
1
2
0
Order By: Relevance
“…Beyond improvements in pain-related symptoms, the enhanced emotional state observed post-HBOT—characterized by reduced PTSD symptoms and depression rates and intensity—may further enhance daily functioning. Those results are in line with previous studies with veterans suffering from combat related PTSD 31 33 as well as the previous results from study done on FMS related CSA 20 , 42 . In longitudinal evaluation of these veterans with combat-related PTSD, it was demonstrated that the beneficial effects of HBOT persisted even two years after treatment 31 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Beyond improvements in pain-related symptoms, the enhanced emotional state observed post-HBOT—characterized by reduced PTSD symptoms and depression rates and intensity—may further enhance daily functioning. Those results are in line with previous studies with veterans suffering from combat related PTSD 31 33 as well as the previous results from study done on FMS related CSA 20 , 42 . In longitudinal evaluation of these veterans with combat-related PTSD, it was demonstrated that the beneficial effects of HBOT persisted even two years after treatment 31 .…”
Section: Discussionsupporting
confidence: 93%
“…A growing body of evidence suggests that the pathophysiological changes resulting from traumatic events can lead to enduring alterations in brain structure and function. These alterations encompass abnormalities in the prefrontal cortex (PFC), the anterior cingulate cortex and the limbic system, as well as impaired connectivity—both functional and structural—between the amygdala, hippocampus, and frontal lobes 33 , 36 , 37 . CSA, characterized by traumatic exposures during maturation, can negatively impact brain development, connectivity, and functionality, making it a risk factor for long-term psychopathology 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation